Membrane platforms for biological nanopore sensing and sequencing. (June 2016) - Schmidt, Jacob
Graphical abstract: Highlights: Biological nanopores enable label-free single molecule sensing. Nanopores have great potential for low cost rapid DNA sequencing. Improved artificial membrane platforms enable nanopore devices and applications. Abstract : In the past two decades, biological nanopores have been developed and explored for use in sensing applications as a result of their exquisite sensitivity and easily engineered, reproducible, and economically manufactured structures. Nanopore sensing has been shown to differentiate between highly similar analytes, measure polymer size, detect the presence of specific genes, and rapidly sequence nucleic acids translocating through the pore. Devices featuring protein nanopores have been limited in part by the membrane support containing the nanopore, the shortcomings of which have been addressed in recent work developing new materials, approaches, and apparatus resulting in membrane platforms featuring automatability and increased robustness, lifetime, and measurement throughput.